The Relationship of Attachment Styles with Childbirth Self-efficacy in Nulliparous Pregnant Women: The Mediating Role of Alexithymia - Marziye Daneshmaram; Sareh Behzadi Pour (Mashhad University of Medical Sciences, 2017)
Background & aim: The enhancement of childbirth self-efficacy to manage the labor pain can help the nulliparous pregnant women to make informed choice about vaginal delivery. Regarding the relationship of the childbirth self-efficacy with psychological antecedents, the present study aimed to explore the meditating role of alexithymia in the relationship of attachment styles and childbirth self-efficacy among the nulliparous pregnant women. Methods: This descriptive correlational study was conducted on 210 nulliparous pregnant women, living in Shiraz in 2016. The samples were selected from the nulliparous women referring to the public and private health and medical centers through the purposive sampling technique. The data were collected using a researcher-made demographic form, Iranian version of Childbirth Self-Efficacy Inventory, Hazan and Shaver's Adult Attachment Inventory, and Farsi Toronto Alexithymia Scale-20. The data analysis was performed using the descriptive statistics and structural equation modeling through the SPSS version 20 and AMOS version 21, respectively. Results: Our findings indicated that all aspects of attachment styles (i.e., secure, avoidant, and ambivalent) would be able to predict the childbirth self-efficacy in the nulliparous pregnant women. On the other hand, the secure and insecure attachment styles predicted alexithymia among this population. The results of the path analysis demonstrated that alexithymia had a mediating role in the relationship of the attachment styles and the childbirth self-efficacy. Conclusion: Based on the findings of the present study, it can be concluded that the attachment styles and childbirth self-efficacy had an indirect relationship mediating through such variables as alexithymia.